Psychosocial aspects of work and musculoskeletal disorders in nursing workers Aspectos psicosociales del trabajo y disturbio músculo-esquelético en trabajadores de enfermería Aspectos psicossociais do trabalho e distúrbio musculoesquelético em trabalhadores de enfermagem - Tânia Solange Bosi de Souza Magnago; Marcia Tereza Luz Lisboa; Rosane Harter Griep; Ana Lúcia Cardoso Kirchhof; Laura de Azevedo Guido (Universidade de São Paulo, 2010)
This study aimed to evaluate the association between psychological demands and control on work and the occurrence of musculoskeletal disorders among nursing workers. This cross-sectional study involved 491 nursing workers from a University hospital in Rio Grande do Sul. Brazilian versions of the Nordic Musculoskeletal Questionnaire and the Job Content Questionnaire were used. Among the participants, 96.3% reported some pain in any given part of the body last year, 73.1% in the last seven days and 65.8% reported difficulty in their daily routine. The chances of shoulder pain (OR=1.97; CI95%=1.07-3.64), in the thoracic spine (OR=1.83; CI95%=1.02-3.35) and in the ankles (OR=2.05; CI95%=1.05-4.02) were higher in the high work demand quadrant when compared to the low demand quadrant, after adjustments for potentially confusing factors Intervention measures in the organizational structure are needed, redefining demand levels and control at work. Este estudio tuvo evaluar la asociación entre demandas psicológicas y el control sobre el trabajo y la ocurrencia de disturbio músculo-esqueléticos en trabajadores de enfermería. Se trata de un estudio transversal, envolviendo 491 trabajadores de enfermería de un hospital universitario en Rio Grande del Sur, en Brasil. Se utilizaron las versiones brasileñas del Nordic Musculoskeletal Questionnaire e del Job Content Questionnaire. De los participantes, 96,3% refirieron dolor en alguna región del cuerpo en el último año, 73,1 % en los últimos siete días y 65,8% relataron dificultades en las actividades diarias. Las probabilidades de dolor fueron: en los hombros (OR=1,97; IC95%=1,07-3,64), en la columna torácica (OR=1,83; IC95%=1,02-3,35) y en los tobillos (OR=2,05; IC95%=1,05-4,02); fueron mayores en el cuadrante de trabajo con alta exigencia si comparado al de baja exigencia, después del ajuste por potenciales factores de confusión. Es necesario adoptar medidas de intervención en la estructura organizacional, redimensionando los niveles de demanda y de control en el trabajo. Este estudo objetivou avaliar a associação entre demandas psicológicas e controle sobre o trabalho e a ocorrência de distúrbios musculoesqueléticos em trabalhadores de enfermagem. Trata-se de estudo transversal, envolvendo 491 trabalhadores de enfermagem de um hospital universitário do Rio Grande do Sul, Brasil. Utilizaram-se versões brasileiras do Nordic Musculoskeletal Questionnaire e do Job Content Questionnaire. Dos participantes, 96,3% referiram dor em alguma região do corpo no último ano, 73,1% nos últimos sete dias e 65,8% relataram dificuldade nas atividades diárias. As chances de dor nos ombros (OR=1,97; IC95%=1,07-3,64), na coluna torácica (OR=1,83; IC95%=1,02-3,35) e nos tornozelos (OR=2,05; IC95%=1,05-4,02) foram maiores no quadrante de trabalho em alta exigência quando se comparou ao de baixa exigência, após ajuste por potenciais fatores de confusão. Faz-se necessária a adoção de medidas interventivas na estrutura organizacional, redimensionando os níveis de demanda e de controle no trabalho.